The authorisation procedure of private security operations in the United Kingdom and the operating structure of private security management in Hungary (Academic Journal of Internal Affairs, 2021)
It can be stated that the legal regulation and the authorisation procedure related to private security activities are stricter in Hungary than in the United Kingdom, because the legislative authority implemented more controlling elements in Hungary. However, it is planned to enforce stricter regulation in relation to the authorisation procedure in the United Kingdom as well. At present, it is only obligatory for natural persons to obtain a license, and the registration of the enterprises is voluntary, but companies possessing an approved status on the listbear a professional service standard and fulfil the requirements of British professional standards. Therefore, it is a kind of a quality guarantee for the clients’ request side. After studying the professional coordination of the National Police Headquarters in Hungary, the system, the operation and the difficulties of the authorisation procedure, my aim was to compare them to the practices in the United Kingdom and collect the good practices from the aspects of crime prevention, efficiency and relief. These good practices ought to be considered, worked out and implemented in the Hungarian private security sector as well.
Keywords: authorisation; authorisation control; professional management of the National Police Headquarters; professional representation of interests